Can green patents reduce carbon emission intensity?—An empirical analysis based on China’s experience - Wang, Na; Yu, Huifang; Shu, Yalin; Chen, Zhao; Li, Tiechen (Frontiers in Environmental Science, 2022)
The study of the effect of green patents on CO2 emission intensity helps to comprehensively understand the strategic value of science and technology innovation for China to achieve "peak carbon" and "carbon neutrality." Furthermore, it offers a reference basis for designing energy conservation and emission reduction policies to achieve better and more precise policies. The paper utilizes annual data on variables such as the number of green invention patents granted, the number of green utility model patents granted, industrial structure, degree of foreign investment introduction, relative energy prices, and energy consumption structure in China from 1993 to 2020 to empirically test the long-term and short-term effects of each factor on CO2 emission intensity by constructing an ARDL model. Research shows there is a significant difference in the effect of green invention patents and green utility model patents on CO2 emission intensity, with green invention patents only contributing to the reduction of carbon emission intensity in the short term but acting as a barrier in the long term. In contrast, green utility model patents suppress carbon emission intensity in the short term but promote the reduction of carbon emission intensity in the long term. In the short term, promoting the policy of "Shrinking the secondary sector and developing the tertiary sector" has the most excellent effect on reducing carbon emission intensity. Increasing the relative price of energy has the second highest effect on reducing carbon emissions intensity. Nevertheless, increasing the degree of foreign investment and the proportion of non-fossil energy is hindering. In the long term, increasing the proportion of non-fossil energy use is crucial to reducing carbon emission intensity in China. In contrast, the relative price of energy does not significantly impact, and increasing the degree of foreign investment is not conducive to reducing carbon emission intensity. Finally, the paper analyzes the policy implications of the empirical results and proposes policy recommendations for simplifying China's CO2 emissions intensity accordingly.